Islam and the of a Middle East - Sohail Mahmood (International Institute of Islamic Thought, 1991)
In her essay, Abul-Fadl argues that the dominant paradigm in the study of the Middle East is inadequate, a view which leads to her assertion that a shift to a new paradigm is required. She maintains that her study is an attempt to create such an alternative outlook, one which surmounts the contemporary ruling paradigm. She suggests that this new paradigm be based solidly on Islam. To begin with, she argues that scholarship on the Middle East must admit the opinion of a native mind and method of argument to the medium of discourse, which itself must become more sensitive and more authentically pluralist if it is to be at all exemplary of historical civilizations and of world truth. Without doubt, such a fresh approach will take some time to develop, for this endeavor requires the rejuvenation of minds and capabilities. As this process begins to take place, Muslims will gradually become more eloquent and capable of readjusting themselves into identifiable and feasible flows so that they can build new schools of thought. She writes that the essay takes the Islamic dimension as a continual factor which goes beyond the transformation of politics at any given age (p. 2), and that acceptance and awareness of variance and multiplicity in the world of politics can only be bonafide and valuable if it is anchored in fidelity to an encompassing congruity which both permeates and surpasses this conglomeration. The encompassing congruity is tawhid. This paradigm is designed by the tawhid episteme and assumes at the outset that those modes, foundations, and parlance are obtained from an Islamic worldview based firmly on the Qur’an and the Sunnah . Abul-Fadl reminds her readers that as a designation, the term “Middle East” is itself dubious and questionable. She uses it to denote a region which is more noticeably specified by its culture then by its territory. The concise nucleus of the region is linguistically Arabic and religiously Muslim, as over nine-tenths of its population shares in the principal cultural marks, values, faith, and customary manners of living. However, current Western political literature on the region has stressed divergence and has insisted in viewing ...